Situation Report: Hungary, 24 January 1983 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Hungarian Party Trying to Reconcile Ideology and Reform / by Alfred Reisch Hungarian Media Silent over Lantos Mission / by Alfred Reisch Military Education in Hungary / by Eva Lengyel County Commissioners to Expend Dollar Exports / by Laszlo Rasko